2021
DOI: 10.1007/s00506-021-00828-3
|View full text |Cite
|
Sign up to set email alerts
|

Die Umsetzung der Kreislaufwirtschaft in österreichischen Unternehmen – Praktiken, Strategien und Auswirkungen auf den Unternehmenserfolg

Abstract: ZusammenfassungDas Konzept der Kreislaufwirtschaft befindet sich seit 2015 als einer der wichtigsten Punkte auf der europäischen Agenda. Infolgedessen wurde auch die Forschung zur Rolle von Unternehmen in der Umstellung auf eine Kreislaufwirtschaft in den letzten Jahren erheblich intensiviert. Bislang wird die wissenschaftliche Literatur jedoch von konzeptionellen Arbeiten dominiert und die verfügbare empirische Forschung besteht hauptsächlich aus Einzel- oder Mehrfachfallstudien. Empirische Studien, die auf g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Changes in the business models are rarely implemented up to now, because the prerequisites are not given (Chiarot et al, 2022). Austrian manufacturing companies try to eliminate inefficiencies in use of material and energy in production lines, and also close internal circular loops to avoid or reuse production waste (Schöggl et al, 2022). As the next strategic milestone, manufacturing companies should attempt to increase their know-how regarding circular economy as well as on the potential benefits that this concept brings for their individual products (Valusyte, 2021).…”
Section: Analysis and Discussion Of The Survey Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Changes in the business models are rarely implemented up to now, because the prerequisites are not given (Chiarot et al, 2022). Austrian manufacturing companies try to eliminate inefficiencies in use of material and energy in production lines, and also close internal circular loops to avoid or reuse production waste (Schöggl et al, 2022). As the next strategic milestone, manufacturing companies should attempt to increase their know-how regarding circular economy as well as on the potential benefits that this concept brings for their individual products (Valusyte, 2021).…”
Section: Analysis and Discussion Of The Survey Resultsmentioning
confidence: 99%
“…Looking at the current implementation of the circular economy in Austria, Schöggl et al found that companies focus mainly on avoiding toxic substances and increasing efficiency (Schöggl et al, 2022). In product design, companies are currently primarily concerned with recycling-oriented product design.…”
Section: Implications For Managers and Practitionersmentioning
confidence: 99%
See 2 more Smart Citations